Economic Effects of Liberalization: The Case of China's Accession to the World Trade Organization - Claustre Bajona; Tianshu Chu (University of Minnesota, Center for Economic Research, 2003)
Many developing economies have joined or applied to join the WTO as part of their process of transformation to market-oriented economies. Accession to the WTO involves provisions to liberalize capital markets and to significantly reduce domestic industrial subsidies to the, usually large, state-owned sector. Therefore, any welfare gains derived from such policies are to be considered as part of the welfare gains of trade liberalization. In this paper we develop a dynamic applied general equilibrium model to quantitatively assess the welfare benefits of capital market liberalization and domestic industrial policy reform, and we apply it to the case of China's accession to the WTO. We find that most of China's benefits of accessing the WTO are derived from the reduction of the state-owned sector driven by the reform in domestic policy required by the treaty. The highest welfare benefits occur when both domestic policy reform and capital market liberalization are jointly implemented. Welfare is enhanced by early opening of the capital markets.
Keywords: 330; Internationale Wirtschaftsorganisation; Mitgliedschaft; Außenhandelsliberalisierung; Makroökonomischer Einfluß; Dynamisches Gleichgewicht; China